(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The purpose o f the article was to demonstrate the threat of metal processing to urban environmental quality and to reveal the peculiarities o f this kind o f pollution. Geochemical data o f topsoil mapping in Panevezys were used for this aim. There has been analysed the input of 16 enterprises involved in this activity to pollution o f Panevezys by Cu, Zn, Pb, Sn, Mo, Ni, Mn, Cr, Ag, Co, as well as Ba, Sr, As, P, U, B, Ga, Ti, V, Zr, Y, Sc. The content o f most elements was determined by DC Arc ES in topsoil fraction